LA REPRESENTACIÓN DE LA MUJER Y LOS ROLES DE GÉNERO EN LOS INFORMATIVOS DEPORTIVOS DE TELEVISIÓN - Elena CALVO ORTEGA (Fonseca, Journal of Communication, 2023)
Television is window to a constructed reality with which not all individuals identify. The reason behind this research lies in the observation of different representation of men and women in sports television news. This article approaches two aspects of representation: the first one is the under-representation of women and the second one addresses how gender roles and traditional stereotypes are passed on through both image and discourse.